HHV-6A/6B Infection of NK Cells Modulates the Expression of miRNAs and Transcription Factors Potentially Associated to Impaired NK Activity - Rizzo, Roberta; Soffritti, Irene; D’Accolti, Maria; Bortolotti, Daria; Di Luca, Dario; Caselli, Elisabetta (Frontiers in Microbiology, 2017)
Natural killer (NK) cells have a critical role in controlling virus infections, and viruses have evolved several mechanisms to escape NK cell functions. In particular, Human herpesvirus 6 (HHV-6) is associated with diseases characterized by immune dysregulation and has been reported to infect NK cells. We recently found that HHV-6 in vitro infection of human thyroid follicular epithelial cells and T-lymphocytes modulates several miRNAs associated with alterations in immune response. Since miRNAs are key regulators of many immune pathways, including NK cell functions, we aimed to study the impact of HHV-6A and -6B in vitro infection on the intracellular mediators correlated to NK cell function. To this purpose, a human NK cell line (NK-92) was infected in vitro with HHV-6A or 6B and analyzed for alterations in the expression of miRNAs and transcription factors. The results showed that both viruses establish lytic replication in NK-92 cells, as shown by the presence of viral DNA, expression of lytic transcripts and antigens, and by the induction of an evident cytopathic effect. Notably, both viruses, although with species-specific differences, induced significant modifications in miRNA expression of miRNAs known for their role in NK cell development, maturation and effector functions (miR-146, miR-155, miR-181, miR-223), and on at least 13 miRNAs with recognized role in inflammation and autoimmunity. Also the expression of transcription factors was significantly modified by HHV-6A/6B infection, with an early increase of ATF3, JUN and FOXA2 by both species, whereas HHV-6A specifically induced a 15-fold decrease of POU2AF1, and HHV-6B an increase of FOXO1 and a decrease of ESR1. Overall, our data show that HHV-6A and -6B infections have a remarkable effect on the expression of miRNAs and transcription factors, which might be important in the induction of NK cell function impairment, virus escape strategies and related pathologies.